The Influence of Learning Motivation and Family Environment on Learning Outcomes Through Learning Activities of Students in the Subject of Social Studies (IPS) at SMPN 4 Mangarabombangy - Alimuddin Alimuddin; Muhammad Rakib; Nawir Rahman (Syntax Idea)
This research aims to determine and analyze: (1) the magnitude of the direct influence of learning motivation on student learning outcomes, (2) the magnitude of the direct influence of the family environment on student learning outcomes, (3) the magnitude of the direct influence of learning activities on student learning outcomes, (4) the magnitude of the influence indirectly, learning motivation and family environment on learning outcomes through student learning activities in social studies subjects at SMPN 4 Mangarabombang. This research is a quantitative research with a research designex post facto type which was held at SMPN 4 Mangarabomban in May - July 2022.The population in this study as many as 257 people with the sampling technique is random sampling with a total sample of 156 people. The procedure for collecting data is through observation and questionnaires. The data analysis techniques used consisted of: (1) Path Analysis, (2) T-test at a 5% alpha significant level. The results showed that; (1) Learning motivation has a significant effect on learning outcomes with the value of t-count < t-table (3.877 > 1.976), (2) Family environment has an effect but not significant on learning outcomes because the value of t-count < t-table (0.313 <1,976) with a value of of0.025, (3) Learning activities have a significant effect on learning outcomes with the value of t-count < t-table (7,749 > 1,976). (4) Learning motivation has an indirect effect on learning outcomes through learning activities of 0.262 greater than the direct effect of 0.257, (5) Family environment has an indirect effect on learning outcomes through learning activities of 0.259 greater than the direct effect, namely 0.021, (6) Simultaneously, learning motivation and family environment have an indirect effect on learning outcomes through learning activities of 0.521 which is also greater than the direct effect on learning outcomes which is only 0.278. (7) In multiple linear regression, the equation of the linear line Y=2,241+0,403X1+0,025X2+0,816X3.